What is Islamic Studies? - Stenberg, Leif (Edinburgh University Press, 2023)
Featuring contributions from anthropologists, historians and scholars of religion, this book explores the passionate, divided and evolving field of Islamic Studies in Europe and North America, past and present – covering topics from secularism and gender to pop music and modern science.